Identification of Significant Proteins in Hypertension Using The Clustering Molecular Complex Detection (MCODE) Method - Setiani, Lusi Agus; Kusuma, Wisnu Ananta; Zulkarnaen, Silvia Alviani (Ilmu Komputer, FMIPA, Universitas Pakuan, 2023)
Hypertension is a condition where the systolic blood pressure value is more than 140 mmHg and the diastolic blood pressure value is more than 90 mmHg. A significant protein is a protein that has the greatest effect or is the center of protein regulation in all biochemical processes. The purpose of this study was to determine the significant protein that has the greatest ef- fect on hypertension by using the clustering Molecular Complex Detection (MCODE) method which will identify areas in the network with the highest density value locally and to determine the mechanism of action of the significant proteins obtained in the setting blood pressure using Gene Ontology and Kyoto Encyclopedia and Genome Analysis (KEGG) by looking at protein signaling pathways for hypertension. The results showed that the STAT3, MAPK3, AKT1, and EDN1 proteins were significant proteins involved in the mechanism of the response to leptin, the ERK1 and ERK2 cascades, the process of nitric oxide biosynthesis, and the cellular response to ROS.